Case Report: Rapid Progression of Cognitive Dysfunction as an Initial Feature of Systemic Lupus Erythematosus With Leukoencephalopathy: A Case Report and Literature Review - Feng, Yukun; Yu, Teng; Xiao, Qin; Yang, Xiaodong (Frontiers in Neurology, 2022)
Neuropsychiatric systemic lupus erythematosus (NPSLE) has been considered to have high morbidity and mortality. Thus, earlier recognition and treatment are of great importance. However, the rapid progression of cognitive dysfunction with leukoencephalopathy as an initial presentation in SLE is rarely described. We report a case in which an elderly man experienced rapidly progressive cognitive impairment with bilateral, symmetric, and diffuse leukoencephalopathy with lasting diffusion-weighted image hyperintensity. An immunological workup showed low complement levels and positivity for antinuclear antibody -speckle and Coombs tests in the patient's serum samples. He had an appropriate improvement in cognitive function after receiving a combination of various immunotherapies. Long-term follow-up showed clinical improvement, including rheumatological labs and neuroimaging. A review of the literature on NPSLE with leukoencephalopathy and a summary of all reported cases to date are also presented. Our case indicated that isolated leukoencephalopathy in NPSLE, as an indicator of severe NPSLE, can be recognized early. Immunotherapy is warranted given the possibility of clinical improvement.